The Routledge companion to Art Deco - Elliott, Bridget 1957-; Windover, Michael (Routledge, Taylor & Francis Group, 2019)
Scholarly interest in Art Deco has grown rapidly over the past fifty years, spanning different academic disciplines. This volume provides a guide to the current state of the field of Art Deco research by highlighting past accomplishments and promising new directions. Chapters are presented in five sections based on key concepts: migration, public culture, fashion, politics, and Art Deco's afterlife in heritage restoration and new media. The book provides a range of perspectives on and approaches to these issues, as well as to the concept of Art Deco itself. It highlights the slipperiness of Art Deco yet points to its potential to shed new light on the complexities of modernity
Keywords: Art Déco; Aufsatzsammlung